Yemen - Road Sector Strategy : Upgrading Public Expenditure, Improving Institutions and Reducing Inefficiencies - Crochet, Jean-Charles (World Bank, Washington, DC, 2012)
Yemen should be credited for achieving an ambitious road building program over the last 25 years, and establishing a large primary road network given its level of Gross Domestic Product (GDP) and population size. With the condition of 60 percent of the paved network rated good or very good, Yemen's road network appears better than in most comparator countries. This positive feature allows the country to satisfy economically its relatively high demand for road transport evidenced by its substantial vehicle fleet and traffic volumes on the arterial network. Yet, the country's inhabitable deserts, mountainous terrain, and population location patterns still give rise to high transport costs and leave many small communities isolated on mountain ridges or in remote valleys. The poor access to markets, employment, and services in many areas pose a serious challenge to economic and social development. The full road sector strategy note takes stock of recent developments in the sector and focuses on performance. It takes into account studies prepared for the Government and the rich dialogue between Government officials and Bank missions over the past few years. Based on this, key issues are identified and recommendations are made on a sector wide, short to medium term, agenda for reform which, if implemented, will further strengthen the performance of the road sector, thereby increasing its contribution to the national economy and the alleviation of poverty.